Politik Pendidikan Islam Pada Masa Kejayaan Dinasti Abbasiyah: Politik Ketenagaan - Kawakib, Nurul (J-PAI: Jurnal Pendidikan Agama Islam, 2014)
Education as a social system, cannot be separated from the other system outside itself, is politic system. Both of them are two important elements in the social politic system of nation. The condition of social politic in the Abbasid era related with politic of manpower. Politic of manpower is education politic tends to be teacher oriented, not institution oriented. It’s mean that the quality of education depends on the quality of teacher, not to institution. It can be evidenced by the condition in which students are free to choose the lesson as they want, they are not only study at mosque, but also at library, private house, and bookstore. They alsochoose a scholarly study or reference by teacher /scholar who teach them, not the institution.keywords: Politic of Islamic Education, Abbasid, Manpower